Exercise-induced molecular mechanisms promoting glycogen supercompensation in human skeletal muscle - Janne R. Hingst; Lea Bruhn; Mads B. Hansen; Marie F. Rosschou; Jesper B. Birk; Joachim Fentz; Marc Foretz; Benoit Viollet; Kei Sakamoto; Nils J. Færgeman; Jesper F. Havelund; Benjamin L. Parker; et al. (Elsevier, 2018)
Objective: A single bout of exercise followed by intake of carbohydrates leads to glycogen supercompensation in prior exercised muscle. Our objective was to illuminate molecular mechanisms underlying this phenomenon in skeletal muscle of man. Methods: We studied the temporal regulation of glycogen supercompensation in human skeletal muscle during a 5 day recovery period following a single bout of exercise. Nine healthy men depleted (day 1), normalized (day 2) and supercompensated (day 5) muscle glycogen in one leg while the contralateral leg served as a resting control. Euglycemic hyperinsulinemic clamps in combination with leg balance technique allowed for investigating insulin-stimulated leg glucose uptake under these 3 experimental conditions. Cellular signaling in muscle biopsies was investigated by global proteomic analyses and immunoblotting. We strengthened the validity of proposed molecular effectors by follow-up studies in muscle of transgenic mice. Results: Sustained activation of glycogen synthase (GS) and AMPK in combination with elevated expression of proteins determining glucose uptake capacity were evident in the prior exercised muscle. We hypothesize that these alterations offset the otherwise tight feedback inhibition of glycogen synthesis and glucose uptake by glycogen. In line with key roles of AMPK and GS seen in the human experiments we observed abrogated ability for glycogen supercompensation in muscle with inducible AMPK deletion and in muscle carrying a G6P-insensitive form of GS in muscle. Conclusion: Our study demonstrates that both AMPK and GS are key regulators of glycogen supercompensation following a single bout of glycogen-depleting exercise in skeletal muscle of both man and mouse. Keywords: AMP-activated protein kinase (AMPK), TBC1 domain family member 4 (TBC1D4), Glycogen synthase (GS), Glucose uptake, Exercise, Insulin action